Peningkatan Nilai Ekonomi Sampah Plastik Melalui Ecobrick di SMK Kewirausahaan Al-Wasath, Kabupaten Lombok Barat - Muhamad Bai'ul Hak; Ali Akbar Hidayat; Ahmad Zaenal Wafik; Rusmin Nuryadin; Al Furkan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The empowerment of society is conducted at a Vocational Boarding School, namely SMK Entrepreneur Al-Wasath. The school is located at West Lombok district. Based on the observation and interview, SMK has a lack of knowledge of plastic waste management and also out of environmental ethics; the school burns the plastic waste. This empowerment aims to explain and demonstrate an effective way to handle the plastic waste through making eco-bricks. Eco-brick is a packing clean and dry plastic waste into a clean plastic bottle.  There are three main stages in this empowerment; the first stage is before empowerment that is observing and interviewing the school to identify the issue of waste. The second stage is implementing the empowerment through  explaining the importance of plastic waste management and the economic value added of eco-brick, and demonstrating how to make the eco-brick. The third stage is evaluation through requesting the participants to complete the eco-brick. From these activities, the participants follow all the process clearly. The empowerment encourages the participants to implement the plastic waste management by making eco-brick in their daily life. Making an eco-brick is not only reducing the volume of plastic waste, but also getting an economic benefit.